Not so different after all: Malaysian researchers' cross-discipline view of quality and trustworthiness in citation practices - Abrizah, Abdullah; Nicholas, D.; Noorhidawati, Abdullah; Yanti Idaya Aspura, M.K.; Badawi, F. (Wiley, 2016)
This paper reports a survey on citation behaviour of Malaysian researchers. It is part of a wider study gauging quality and trustworthiness in scholarly communication in the emerging digital environment. The survey questionnaire was distributed between 1 October 2014 and 31 January 2015. A total of 391 respondents, from four research areas (humanities, life sciences, physical sciences, and social sciences) completed the questionnaire. The finding indicated that motivations for citing were complex and multi-faceted, but in all four disciplines, researchers cite a work because they regard it as an authoritative and trustworthy source, which provides a context or building block to their own research. Although researchers have moved from a print-based system to a digital one, it has not significantly changed the way they decide what to trust. Peer reviewed journals are still the most influential. Open access journals will be cited if they have been peer reviewed. Citing on the basis of high altmetrics and other social judgements, such as mentions, likes, and use, was not prevalent. Measures of establishing trust and authority do not seem to have changed profoundly in Malaysia.